2023
DOI: 10.1093/plphys/kiad361
|View full text |Cite
|
Sign up to set email alerts
|

The functions of a 5′ tRNA-Ala-derived fragment in gene expression

Abstract: Transfer RNA (tRNA) can produce smaller RNA fragments called tRNA-derived fragments (tRFs). tRFs play critical roles in multiple cellular programs, although the functional mechanisms of tRFs remain largely unknown in plants. In this study, we examined the phenotype associated with 5′ tRF-Ala (tRF-Ala, produced from tRNA-Ala) overexpression and knockdown lines (tDR-Ala-OE and tDR-Ala-kd, respectively) and the mechanisms by which tRF-Ala affects mRNA levels in Arabidopsis (Arabidopsis thaliana). We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…A more comprehensive study later revealed that only a subset of the Arabidopsis tRFs can interfere with translation (Lalande et al ., 2020). Based on A. thaliana overexpression and knockdown lines, a recent paper reported that the 5′‐tRF Ala‐TGC associates with a splicing factor (SR34), resulting in a set of genes with altered transcript levels and differentially spliced transcript variants (Li et al ., 2023). The latter work might point at additional, presently understudied roles for tRFs in the context of plant biology.…”
Section: Putative Trf and Rrf Functions In Plant–microbe Interactionsmentioning
confidence: 99%
“…A more comprehensive study later revealed that only a subset of the Arabidopsis tRFs can interfere with translation (Lalande et al ., 2020). Based on A. thaliana overexpression and knockdown lines, a recent paper reported that the 5′‐tRF Ala‐TGC associates with a splicing factor (SR34), resulting in a set of genes with altered transcript levels and differentially spliced transcript variants (Li et al ., 2023). The latter work might point at additional, presently understudied roles for tRFs in the context of plant biology.…”
Section: Putative Trf and Rrf Functions In Plant–microbe Interactionsmentioning
confidence: 99%
“…B) Stress-induced tDR-Ala-5D plays roles in regulating mRNA splicing and protein translation. Li et al (2023) show that tDR-Ala-5D interacts with the splicing factor SR34 and interferes with precursor mRNA alternative splicing of crucial genes associated with stress responses. A previous work by Ivanov et al (2011) demonstrated that tDR-Ala-5D also binds to the translation initiation complex eIF4F, which results in attenuated protein synthesis in response to stress.…”
mentioning
confidence: 92%
“…Progress in this field has brought exciting changes to the paradigm of RNA world. In this issue of Plant Physiology , Li et al (2023) found new functions of a plant tDR in stress responses via interacting with the mRNA splicing factor SERINE-ARGININE RICH PROTEIN 34 (SR34).…”
mentioning
confidence: 99%
See 2 more Smart Citations